2010
DOI: 10.1111/j.1745-9125.2010.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Conceptual Issues in Testing the Race–crime Invariance Thesis: Black, White, and Hispanic Comparisons*

Abstract: Our goal in this article is to contribute conceptually and empirically to assessments of the racial invariance hypothesis, which posits that structural disadvantage predicts violent crime in the same way for all racial and ethnic groups. Conceptually, we elucidate the scope of the racial invariance hypothesis and clarify the criteria used for evaluating it. Empirically, we use 1999–2001 averaged arrest data from California and New York to extend analyses of the invariance hypothesis within the context of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
137
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(155 citation statements)
references
References 38 publications
13
137
0
5
Order By: Relevance
“…To account for county socioeconomic conditions, we created a concentrated disadvantage index using principal components analysis to combine four commonly used disadvantage indicators (see Land, McCall, and Cohen 1990;Steffensmeier et al 2010): poverty (percentage of population below the poverty line), unemployment (percentage of the 16-59 civilian labor force unemployed), female headship (percentage of families with children under 18 headed by a female), and low education (percentage of residents 25þ without a high school degree). In addition, because of their demonstrated relevance in previous studies, we include as controls: residential mobility (percentage of households that experience housing turnover during the 2005-2010 period); an entropy score of racial=ethnic heterogeneity as a measure of population diversity (Reardon and Firebaugh 2002); logged population density; and percent urban.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for county socioeconomic conditions, we created a concentrated disadvantage index using principal components analysis to combine four commonly used disadvantage indicators (see Land, McCall, and Cohen 1990;Steffensmeier et al 2010): poverty (percentage of population below the poverty line), unemployment (percentage of the 16-59 civilian labor force unemployed), female headship (percentage of families with children under 18 headed by a female), and low education (percentage of residents 25þ without a high school degree). In addition, because of their demonstrated relevance in previous studies, we include as controls: residential mobility (percentage of households that experience housing turnover during the 2005-2010 period); an entropy score of racial=ethnic heterogeneity as a measure of population diversity (Reardon and Firebaugh 2002); logged population density; and percent urban.…”
Section: Control Variablesmentioning
confidence: 99%
“…However, to account for places with low counts of homicides, we utilize negative binomial models that take into account the presence of zero counts (see description of analytic techniques). Diagnostic tests regarding the appropriateness of zero-inflated models revealed that standard negative binomial models were more appropriate.7 Unfortunately, Hispanic-specific violence measures are rare, where most databases, including the Uniform Crime Reports, count Hispanics within the more traditional white, black, Asian, and Native American racial categories(Steffensmeier et al 2010).HISPANIC IMMIGRATION, RELIGION, AND CRIME…”
mentioning
confidence: 99%
“…have lower rates of violence than would be expected given the levels of disadvantage they experience (Feldmeyer, 2010;Martinez, 2002;Sampson, 2008; also see review in Shihadeh & Barranco, 2010). Building on such observations, scholars have posited that structural disadvantage is more weakly associated with Latino violence than for other groups because protective elements of Latino culture-greater emphasis on family, community, cultural identity, and heritage-promote social organization, group cohesion, and facilitate ties that may buffer the effects of disadvantage on violence (Feldmeyer & Steffensmeier, 2009;Light & Gold, 2000;Martinez, 2002;Massey, 2008;Tienda & Mitchell, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…At the same time, we acknowledge another possible outcome predicted by the racial invariance thesis (see reviews in Parker, 2008;Steffensmeier, Ulmer, Feldmeyer, & Harris, 2010). Informing much of the race-specific criminological research to date, this position argues that racial/ethnic differences in violence are the product of differential exposure to criminogenic structural conditions (particularly disadvantage) across racial/ethnic groups and that these structural predictors are associated with crime in the same manner for all demographic subgroups (Ousey, 1999).…”
Section: Changes In Latino Settlement: Does the Paradox Persist?mentioning
confidence: 95%
See 1 more Smart Citation